The Chondroprotective Role of TMF in PGE2-Induced Apoptosis Associating with Endoplasmic Reticulum Stress. (7th September 2015) - Yang, Jianqiong; Liu, Haiqing; Li, Linfu; Liu, Hai; Shi, Weimei; Wu, Longhuo
Abstract : Endoplasmic reticulum stress (ERS) has been demonstrated to exhibit a critical role in osteoarthritic chondrocytes. Whether 5, 7, 3′, 4′-tetramethoxyflavone (TMF) plays the chondroprotective role in inhibition of PGE2 -induced chondrocytes apoptosis associating with ERS has not been reported. To investigate this, the activation of PERK, ATF6, and IRE1 signaling pathways in ERS in chondrocytes pretreated with PGE2 was studied. By treatment with PGE2, the chondrocytes apoptosis was significantly increased, the proapoptotic CHOP and JNK were upregulated, the prosurvival GRP78 and XBP1 were downregulated, and GSK-3 β was also upregulated. However, TMF exhibited the effectively protective functions via counteracting these detrimental effects of PGE2 . Finally, the inflammatory cytokine PGE2 can activate ERS signaling and promote chondrocytes apoptosis, which might be associated with upregulation of GSK-3 β . TMF exhibits a chondroprotective role in inhibiting PGE2 -induced ERS and GSK-3 β .